Pregnancy and Birth Traditions: Living Hadith Study ff Sambas Malay Life Cycle - Masmuri Masmuri; Bayu Suratman (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
Research conducted on the Malay community in Sambas Regency, West Kalimantan Province focused on the tradition of pregnancy and birth of the Sambas Malays as a tradition based on hadith or called living hadith. In addition, the tradition carried out by the Sambas Malays can be categorized as a living hadith phenomenon because the purpose of the tradition of pregnancy and birth is a form of gratitude for the Sambas Malays for the presence of the fetus they are carrying and being grateful for the birth of a child. The tradition of pregnancy and birth is part of the representation of their inherent identity as adherents of Muhammad's teachings, but on the other hand they also carry out local traditions. For the Sambas Malays, traditions do not contradict and even become a necessity in their community. This research is a qualitative-descriptive study where the data were obtained based on the results of interviews, observations, and documentation conducted on the Sambas Malays in Sambas Regency. and give birth. As adherents of Islamic teachings who adhere to the Sambas Malay community, they include Islamic values ​​in their implementation so that there is no conflict between the two. The tradition of pregnancy and childbirth by the Malay sambas is based on and based on the hadith of the Prophet Muhammad